Preparation method and application of cationic polyurethane / carboxyl carbon nanotube conductive composite foam
By preparing cationic polyurethane/carboxycarbon carbon nanotube conductive composite foam, the problems of insufficient flexibility and sensitivity in existing strain sensors in flexible and wearable applications are solved, and the performance of high sensitivity and wide strain sensing range is achieved, and it is suitable for applications such as human motion detection.
Patent Information
- Application Number
- CN202411107179.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-13
AI Technical Summary
Existing strain sensors have problems with insufficient flexibility and insufficient sensitivity in flexible and wearable applications, making it difficult to effectively detect minor strain changes.
By preparing cationic polyurethane/carboxycarbon carbon nanotube conductive composite foam, the cationic groups and carboxycarbon carbon nanotubes form an electrostatic interaction, improve the binding ability of nanofillers and polyurethane foam, and enhance the porous structure of the foam to improve sensitivity.
It achieves high sensitivity and wide strain sensing range, excellent mechanical performance, and is suitable for applications such as human motion detection, and has the advantages of light weight, high flexibility, and breathability.
Smart Images

Figure CN118955994B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wearable flexible electronics and relates to a preparation method and application of a cationic polyurethane / carboxyl carbon nanotube conductive composite foam. Background Art
[0002] With the rapid development of intelligent electronic technology, flexible electronic devices have become a hot topic of research due to their unique flexibility, wearability and compatibility with human skin. As an important component of flexible electronic devices, flexible strain sensors have attracted much attention due to their ability to accurately detect tiny deformations. Such sensors can convert mechanical strain into electrical signals, providing key input information for intelligent systems.
[0003] Traditional strain sensors are usually made of rigid materials, which limits their use in flexible and wearable applications. In contrast, flexible strain sensors use elastomeric materials such as polymers, silicones or nanocomposites, which not only have good flexibility and stretchability, but can also withstand large deformations while maintaining high sensitivity. In addition, the design of flexible strain sensors usually takes ergonomics and biocompatibility into consideration, allowing them to be seamlessly integrated with human skin and provide a comfortable wearing experience.
[0004] Strain sensors need to have a series of basic properties such as high stretchability, good sensitivity, wide sensing range, good stability, and good repeatability. These performance characteristics ensure that the sensor can accurately sense and capture strain changes from subtle to significant, and can maintain its performance during long-term use. Among them, high sensitivity and a wide strain sensing range are two important parameters of sensing performance, which ensure that the sensor can detect strain changes from subtle to significant; and good stability and repeatability ensure that the strain sensor can be used for a long time. In order to improve these properties, most studies focus on introducing covalent bonds and hydrogen bonds into the system to improve mechanical properties, or improving the cooperative deformation ability of the polymer matrix or substrate and the conductive network through structural design or interaction, so as to achieve the purpose of enhancing sensor performance.
[0005] Here, we fabricated a foam-shaped strain sensor composed of cationic polyurethane and carboxyl multi-walled carbon nanotubes (MWCNTs) by combining salt template and dip-coating methods. The obtained CPU / MWCNTs-C foam sensor has a wide strain sensing range (~100%), high sensitivity (GF=5.0) and long-lasting cyclic stability, which is suitable for monitoring various human motions. In addition, the sensor has other advantages such as light weight, high flexibility and high breathability. It has great potential in the field of wearable electronics in the future. Summary of the invention
[0006] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a cationic polyurethane / carboxyl carbon nanotube conductive composite foam and its application. The cationic polyurethane prepared by using a diol chain extender containing a cationic group, a bifunctional small molecule chain extender containing a hydroxyl group or an amino group, and an isocyanate-terminated polyurethane prepolymer as main raw materials includes a hard segment structure with a cationic group and a soft segment structure with a strong polarity. Cationic groups are introduced into the hard segment main chain structure to form electrostatic interactions with carboxyl carbon nanotubes, thereby promoting the binding ability between nanofillers and polyurethane foam. The porous structure of the foam improves the sensitivity of the assembled sensor within a small strain range, and is expected to be applied to the field of human motion detection.
[0007] In order to achieve the above purpose, this application adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a cationic polyurethane / carboxyl carbon nanotube conductive composite foam, comprising the following steps:
[0009] (1) Preparation of cationic polyurethane: In an inert gas environment, firstly, a polyether or polyester diol and a diisocyanate are subjected to a thermal polymerization reaction under the catalysis of a catalyst to generate an isocyanate-terminated polyurethane prepolymer, and an organic solvent is added to reduce the viscosity of the system and the temperature at the same time; then, a diol chain extender containing a cationic group, a bifunctional small molecule chain extender containing a hydroxyl group or an amino group and the polyurethane prepolymer are dissolved in N,N-dimethylformamide for further heating reaction, and the product is washed and dried to obtain a cationic polyurethane;
[0010] (2) dissolving the cationic polyurethane in an organic solvent, adding an inorganic salt and mixing, then pouring the mixture into a mold, drying to obtain a cationic polyurethane / inorganic salt composite elastomer, and soaking the composite elastomer in water to dissolve the inorganic salt inside and leave pores, thereby obtaining a cationic polyurethane foam;
[0011] (3) Soaking the cationic polyurethane foam in a carboxyl carbon nanotube aqueous solution, taking it out, washing and drying it to obtain the cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0012] In the above technical scheme, the inert gas in step (1) is preferably nitrogen, the thermal polymerization reaction temperature is 60-90°C, and the reaction time is 2-4h. The polymer chain extension reaction temperature is 60-80°C, and the reaction time is 1-5h. The washing conditions are water or ethanol washing, and the drying conditions are 60-90°C, 24-48h.
[0013] The molar ratio of the total of the polyether or polyester diol, diisocyanate and chain extender is 0.2-0.5:1:0.5-0.8; the molar ratio of the diol chain extender to the difunctional small molecule chain extender is 0.25-4.0:1.
[0014] In the above technical scheme, the polyether or polyester diol in step (1) is one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polycaprolactone diol, polyoxalic acid-1,4-butanediol, and polycarbonate diol, and the average molecular weight is 800-2000g / mol;
[0015] The diisocyanate is one or more of hexamethylene diisocyanate, toluene-2,4-diisocyanate, 4,4-diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, and m-phenylene diisocyanate; preferably hexamethylene diisocyanate, and its structural formula is as follows:
[0016]
[0017] The diol chain extender is one of N, N-bis (2-hydroxyethyl) -N-methylethane-1-ammonium bromide and N, N-bis (2-hydroxyethyl) -N-methylpropane-1-ammonium bromide;
[0018] The bifunctional small molecule chain extender is a bifunctional alcohol or amine compound containing hydroxyl or amino groups, and is one or more of 1,4-butanediol, ethylene glycol, hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, diethyltoluene diamine, and isophorone diamine.
[0019] In the above technical solution, the catalyst in step (1) is one or more of dibutyltin dilaurate, stannous isooctanoate, pentamethyldiethylenetriamine, and dimethylcyclohexylamine, and the amount used is 0.1-1wt% of the prepolymer mass, preferably dibutyltin dilaurate.
[0020] In the above technical scheme, the organic solvent in step (1) and step (2) is one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, preferably N,N-dimethylformamide.
[0021] In the above technical solution, in step (1), the mass concentration of the polyurethane prepolymer is 20 to 50 wt%.
[0022] In the above technical solution, in step (2), the dissolving temperature is 30-60°C, the dissolving time is 2-5h, the drying temperature is 25-50°C, and the drying time is 2-6h.
[0023] The inorganic salt is one or more of sodium chloride, potassium chloride, calcium chloride and magnesium chloride, and the mass of the inorganic salt is 20-120% of the mass of the cationic polyurethane, preferably sodium chloride.
[0024] In the above technical solution, the concentration of the carboxyl carbon nanotube aqueous solution in step (3) is 0.01-0.05 g / mL, the soaking time is 3-12 hours, the drying temperature is 25-50° C., and the drying time is 2-6 hours.
[0025] In a second aspect, the present invention provides the use of the cationic polyurethane / carboxyl carbon nanotube conductive composite foam prepared by the above preparation method in the preparation of a strain sensor, wherein the strain sensor is a flexible resistance sensor for real-time monitoring of human body movement.
[0026] The beneficial effects of the present invention are:
[0027] (1) The cationic polyurethane of the present invention comprises a hard segment structure having a cationic group and a soft segment structure with a strong polarity, wherein the introduction of the cationic group on the main chain of the hard segment increases the interaction force and hydrophilicity between the cationic polyurethane and the acidified carbon nanotubes, and can promote the dispersion of the acidified carbon nanotubes in the cationic polyurethane substrate.
[0028] (2) Due to the presence of carbamate bonds and quaternary ammonium salt cationic groups, the cationic polyurethane of the present invention can form hydrogen bonds, electrostatic forces, cation-π and other interactions with carboxyl, amino, benzene ring, hydroxyl, carboxylate and other groups on the substrate, providing a certain adhesion ability to the substrate.
[0029] (3) The cationic polyurethane / carboxyl carbon nanotube conductive composite foam of the present invention has excellent mechanical properties, with a mechanical strength of 1.92 MPa and an elongation at break of 475%. It also has a relatively low density and certain air permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The Fourier transform infrared spectra of the cationic polyurethane prepared in Examples 1 to 4 are as follows:
[0031] Figure 2 It is a mechanical property curve diagram of the cationic polyurethane prepared in Examples 1 to 4 at room temperature and pressure.
[0032] Figure 3 Adhesion properties of the cationic polyurethane prepared in Example 3
[0033] Figure 4 The mechanical properties of the cationic polyurethane, cationic polyurethane foam and cationic polyurethane / carboxyl carbon nanotube conductive composite foam prepared in Example 3 are shown.
[0034] Figure 5 This is the strain sensing performance of the cationic polyurethane / carboxyl carbon nanotube conductive composite foam prepared in Example 3. DETAILED DESCRIPTION
[0035] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0036] Example 1 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0037] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0038] 0.242 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.36 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise. The reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer, named CPU1.
[0039] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0040] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0041] Example 2 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0042] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0043] 0.484 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.27 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise. The reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer, named CPU2.
[0044] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0045] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0046] Example 3 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0047] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0048] 0.726 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.18 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise. The reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer, named CPU3.
[0049] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0050] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0051] Example 4 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0052] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0053] 0.964 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.09 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise. The reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer, named CPU4.
[0054] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0055] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0056] Example 5 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0057] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0058] 0.726 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.18 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise, and the reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer.
[0059] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.4 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0060] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0061] Example 6 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0062] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0063] 0.726 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.18 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise, and the reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer.
[0064] Add 1 g of cationic polyurethane elastomer into a flask containing 10 mL of tetrahydrofuran, stir and dissolve at 60°C for 2 h, then add 1.2 g of sodium chloride, continue stirring at room temperature for 2 h, pour the solution into a mold, evaporate the solvent at room temperature for 5 h, and then soak the obtained sample in 60°C hot water for 3 h to remove the sodium chloride to obtain a cationic polyurethane foam.
[0065] The cationic polyurethane foam was immersed in a 0.01 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0066] Example 7 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0067] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0068] 0.726 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.18 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise, and the reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer.
[0069] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0070] The cationic polyurethane foam was immersed in a 0.03 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0071] Example 8 Preparation of Cationic Polyurethane / Carboxyl Carbon Nanotube Conductive Composite Foam
[0072] 10.0 g of dehydrated polytetrahydrofuran-2000, 1.682 g of hexamethylene diisocyanate and 0.01 g of dibutyltin dilaurate were added to a container, and the mixture was heated to 80° C. and reacted for 3 h to obtain a prepolymer having an isocyanate terminal group. 10 mL of N,N-dimethylformamide was added to reduce the viscosity, and the temperature was lowered to 60° C.
[0073] 0.726 g of N, N-bis(2-hydroxyethyl)-N-methylpropane-1-ammonium bromide and 0.18 g of 1,4-butanediol were dissolved in 25 mL of N, N-dimethylformamide, and the polyurethane prepolymer was added dropwise, and the reaction was continued to obtain a polyurethane elastomer solution. The polyurethane elastomer solution was washed with a large amount of deionized water and vacuum dried to obtain a cationic polyurethane elastomer.
[0074] 1 g of cationic polyurethane elastomer was added to a flask containing 10 mL of tetrahydrofuran, and dissolved by stirring at 60°C for 2 h. Then, 0.8 g of sodium chloride was added and stirred at room temperature for 2 h. The solution was poured into a mold, and the solvent was evaporated at room temperature for 5 h. Then, the obtained sample was immersed in hot water at 60°C for 3 h to remove the sodium chloride, thereby obtaining a cationic polyurethane foam.
[0075] The cationic polyurethane foam was immersed in a 0.05 g / mL carboxyl carbon nanotube aqueous solution for 6 h to obtain a cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
[0076] Performance Characterization
[0077] Fourier transform infrared spectroscopy
[0078] The cationic polyurethanes prepared in Examples 1-4 were tested using Fourier transform infrared (FT-IR Nicolet 6700) at room temperature and pressure. Figure 1 As shown in the figure, with the increase of cationic chain extender content, the intensity of (C=O) and (-NH) hydrogen bond peaks decreases, and the quaternary ammonium salt group (CH3-N + and -CH2-N + )’s strength increases.
[0079] Mechanical properties test
[0080] At room temperature and pressure, the mechanical properties of the cationic polyurethanes prepared in Examples 1-4 were tested using a universal testing machine (Instron MODEL 5567) at a tensile speed of 50 mm / min. Figure 2 As shown, the mechanical properties of polyurethane can be changed by adjusting the ratio of soft and hard segments.
[0081] Adhesion performance test of cationic polyurethane
[0082] The adhesion performance of the cationic polyurethane prepared in Example 3 was measured by lap shear adhesion test. The cationic polyurethane was sandwiched between two test materials (iron sheet, aluminum sheet, glass, wood, organic glass and plastic) and closely attached, and measured at a tensile speed of 50 mm / min using a high and low temperature dual column tester (Instron 5966) of Instron Company, USA. The adhesion strength was calculated according to the formula.
[0083] Sensing performance test of cationic polyurethane / carboxyl carbon nanotube conductive composite foam
[0084] The sensing performance is measured by resistance change on a digital Bluetooth multimeter (ZOYI-300AB). The conductive composite foam is cut into strips of 40mm×2mm×0.8mm, connected to the multimeter through two copper wires, and then placed on the index finger for testing to detect human movement. The resistance change is the real-time resistance minus the initial resistance.
[0085] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a cationic polyurethane / carboxyl carbon nanotube conductive composite foam, characterized in that: The following steps are involved: (1) Preparation of cationic polyurethane: In an inert gas environment, firstly, a polyether or polyester diol and a diisocyanate are subjected to a thermal polymerization reaction under the catalysis of a catalyst to generate an isocyanate-terminated polyurethane prepolymer, and an organic solvent is added; then, a diol chain extender containing a cationic group, a bifunctional small molecule chain extender containing a hydroxyl group or an amino group, and the polyurethane prepolymer are dissolved in N,N-dimethylformamide for further heating reaction, and the product is washed and dried to obtain a cationic polyurethane; (2) dissolving the cationic polyurethane in an organic solvent, adding an inorganic salt and mixing, then pouring the mixture into a mold, drying to obtain a cationic polyurethane / inorganic salt composite elastomer, and soaking the composite elastomer in water to dissolve the inorganic salt inside and leave pores, thereby obtaining a cationic polyurethane foam; (3) Soaking the cationic polyurethane foam in a carboxyl carbon nanotube aqueous solution, taking it out, washing and drying it to obtain the cationic polyurethane / carboxyl carbon nanotube conductive composite foam.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the total of the polyether or polyester diol, diisocyanate and chain extender in step (1) is 0.2-0.5:1:0.5-0.8; the molar ratio of the diol chain extender to the difunctional small molecule chain extender is 0.25-4.0:
1.
3. The preparation method according to claim 1, characterized in that: The polyether or polyester diol in step (1) is one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polycaprolactone diol, polyoxalic acid-1,4-butanediol, and polycarbonate diol, and has an average molecular weight of 800-2000 g / mol; The diisocyanate is one or more of hexamethylene diisocyanate, toluene-2,4-diisocyanate, 4,4-diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, and m-phenylene diisocyanate; The diol chain extender is one of N, N-bis (2-hydroxyethyl) -N-methylethane-1-ammonium bromide and N, N-bis (2-hydroxyethyl) -N-methylpropane-1-ammonium bromide; The bifunctional small molecule chain extender is a bifunctional alcohol or amine compound containing hydroxyl or amino groups, and is one or more of 1,4-butanediol, ethylene glycol, hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, diethyltoluene diamine, and isophorone diamine.
4. The preparation method according to claim 1, characterized in that: The catalyst in step (1) is one or more of dibutyltin dilaurate, stannous isooctanoate, pentamethyldiethylenetriamine, and dimethylcyclohexylamine, and the amount used is 0.1-1wt% of the prepolymer mass.
5. The preparation method according to claim 1, characterized in that: In step (1), the organic solvent in step (2) is one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
6. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the polyurethane prepolymer is 20 to 50 wt%.
7. The preparation method according to claim 1, characterized in that: The inorganic salt in step (2) is one or more of sodium chloride, potassium chloride, calcium chloride and magnesium chloride, and the mass of the inorganic salt is 20 to 120% of the mass of the cationic polyurethane.
8. The preparation method according to claim 1, characterized in that: The concentration of the carboxyl carbon nanotube aqueous solution in step (3) is 0.01-0.05 g / mL.
9. Use of the cationic polyurethane / carboxyl carbon nanotube conductive composite foam prepared by the preparation method according to any one of claims 1 to 8 in the preparation of a strain sensor, wherein the strain sensor is a flexible resistance sensor for real-time monitoring of human body movement.